2002
DOI: 10.1080/00222890209601938
|View full text |Cite
|
Sign up to set email alerts
|

Perceptual-Motor Contributions to Static and Dynamic Balance Control in Children

Abstract: ABSTRACT. The authors addressed balance control in children from the perspective of skill development and examined the relationship between specific perceptual and motor skills and static and dynamic balance performance. Fifty 11-to 13-year-old children performed a series of 1-legged balance tasks while standing on a force platform. Postural control was reflected in the maximum displacement of the center of mass in anterior-posterior and mediolateral directions. Simple visual, discrimination, and choice reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
67
1
4

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(80 citation statements)
references
References 37 publications
8
67
1
4
Order By: Relevance
“…More specifically, maximal amplitude and mean velocity of CoP displacements decreased between 4-5 and 6-7 years, reached a plateau around the ages of 6-11 years, and decreased again between 10-11 years and adult age. These results confirmed that (1) the improvement of postural control during childhood is characterized by a decreasing magnitude (i.e., Hatzitaki et al 2002), and frequency (i.e., Figura et al 1991) of postural sway, (2) the period of 8-11 years can be considered as a critical period (Rival et al 2005) resulting from an integration of the reactive and predictive modes of postural control (Riach and Starkes 1994), from a better integration of sensory information (Baumberger et al 2004), and from the apparition of adult-like balance control strategies characterized by a head-trunk coordination (Assaiante and Amblard 1995), and (3) the adults' level is still not reached at the age of 11.…”
Section: Discussionsupporting
confidence: 81%
“…More specifically, maximal amplitude and mean velocity of CoP displacements decreased between 4-5 and 6-7 years, reached a plateau around the ages of 6-11 years, and decreased again between 10-11 years and adult age. These results confirmed that (1) the improvement of postural control during childhood is characterized by a decreasing magnitude (i.e., Hatzitaki et al 2002), and frequency (i.e., Figura et al 1991) of postural sway, (2) the period of 8-11 years can be considered as a critical period (Rival et al 2005) resulting from an integration of the reactive and predictive modes of postural control (Riach and Starkes 1994), from a better integration of sensory information (Baumberger et al 2004), and from the apparition of adult-like balance control strategies characterized by a head-trunk coordination (Assaiante and Amblard 1995), and (3) the adults' level is still not reached at the age of 11.…”
Section: Discussionsupporting
confidence: 81%
“…Dynamic balance tasks, therefore, have been increasingly recommended recently to monitor functional recovery after injury, since they are believed to reflect the underlying mechanism of postural control strategies utilized in daily life activities (15,16). Hatzitaki et al (17), for example, have shown that balance performance under quiet standing tasks is mostly related to perceiving and processing visual inputs, whereas maintaining balance under dynamically demanding tasks depends highly on rapid processing of somatosensory afferences and initiation of corrective motor responses. They also indicated that under dynamic conditions, the postural control system adapts predictive control strategies (i.e., anticipatory postural adjustments), in which sensory signals from the proprioceptive system need to be processed in a feedforward manner to project expected COM deviations with respect to internal references and external perturbations.…”
Section: Introductionmentioning
confidence: 99%
“…Developmentally, the ability to perform either type of tasks becomes adult-like between 7 and 10 y of age [2]. This type of performance coincides with mastery of different motor control mechanisms (e.g., open, closed or integrated type of control) [3], and associated sensory [4] motor sub-systems [5]. Traditionally, it has been assumed that balance control, particularly static, is automatic and it can be maintained in the absence of attention.…”
Section: Introductionmentioning
confidence: 99%